2010
DOI: 10.1177/039463201002300123
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Anti-TNF-α Treatments Reverse the Endothelial Dysfunction in Rheumatoid Arthritis: The Biological Coherence between Synovial and Endothelial Inflammation

Abstract: Rheumatoid arthritis (RA) is associated with an excess cardiovascular morbidity and mortality, related to systemic inflammation with endothelial dysfunction (ED) and impaired flow-mediated vasodilation (FMD). We assessed the FMD response to anti-TNF-a treatments in 28 RA patients, aged 49.8±15.3 years: an unpaired FMD was found in 66.7% of our cases and was restored after 6 weeks of anti-TNF-a treatment (13.5±5.3% vs 4.6±4.1 %, p < 0.05). Twenty-five percent of the infliximab patients demonstrated a long term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Several studies have shown that the levels of TNF-α correlated with arthritis severity, and that TNF-α neutralizing therapy using Anti-TNF-α monoclonal antibody and soluble TNF receptor improves clinical symptoms and inhibits (or even reverses) inflammatory bone destruction in RA . In synovial tissue of RA patients, a positive regulatory cycle is produced whereby NF-κB induces the transcription of pro-inflammatory cytokines such as TNF-α, and cell adhesion molecules (Capria et al, 2010). Moreover, our previous study has demonstrated this upon treatment with AR-6 in CIA rats.…”
Section: Discussionmentioning
confidence: 85%
“…Several studies have shown that the levels of TNF-α correlated with arthritis severity, and that TNF-α neutralizing therapy using Anti-TNF-α monoclonal antibody and soluble TNF receptor improves clinical symptoms and inhibits (or even reverses) inflammatory bone destruction in RA . In synovial tissue of RA patients, a positive regulatory cycle is produced whereby NF-κB induces the transcription of pro-inflammatory cytokines such as TNF-α, and cell adhesion molecules (Capria et al, 2010). Moreover, our previous study has demonstrated this upon treatment with AR-6 in CIA rats.…”
Section: Discussionmentioning
confidence: 85%
“…A broad range of stimuli including the cytokines, TNF-a or IL-1b, and chemokines activate the NF-kB dimers by triggering a signaling pathway that leads to the phosphorylation of IkB. In synovial tissue of RA patients, a positive regulatory cycle is produced whereby NF-jB induces the transcription of pro-inflammatory cytokines, such as IL-1b and TNF-a, chemokines, and cell adhesion molecules and promotes the expression of COX-2, iNOS and MMPs in many cell types [13]. Moreover, the overexpression of inflammatory factors has been shown to induce the activation of NF-jB in the positive feedback loop [13].…”
Section: Discussionmentioning
confidence: 99%
“…In synovial tissue of RA patients, a positive regulatory cycle is produced whereby NF-jB induces the transcription of pro-inflammatory cytokines, such as IL-1b and TNF-a, chemokines, and cell adhesion molecules and promotes the expression of COX-2, iNOS and MMPs in many cell types [13]. Moreover, the overexpression of inflammatory factors has been shown to induce the activation of NF-jB in the positive feedback loop [13]. In the present study, the expression of p-p65 (activated NF-jB subunit), p-IKBa and p-IKBb was measured to determine whether NF-jB is activated in RASF stimulated by LPS.…”
Section: Discussionmentioning
confidence: 99%
“…103 Decreased FMD correlates well with invasive tests of coronary endothelial dysfunction and atherosclerosis, and predicts CV events in population-based studies. 104,105 In patients with inflammatory arthritis, most studies revealed transient [106][107][108][109] or even sustained ($12 weeks) [110][111][112][113][114][115] improvement in macrovascular function by anti-TNF treatment, whereas only 3 studies found no improvement. 75,95,116 In a study comparing anti-TNF treatment and traditional DMARDs, more significant improvement in FMD was observed in the anti-TNF group.…”
Section: Mechanism Of Inflammation In Cvd In Inflammatorymentioning
confidence: 99%